Factors influencing pricing of tea at colombo auction - Sampath, T.; Sooriyakumar, K.; Sarujan, S. (University of Jaffna, 2017)
Tea industry in Sri Lanka is currently experiencing a decline in tea prices and a high cost of production along with low productivity. The smallholder tea sector continued to dominate the overall tea industry contributing over 73 per cent to total tea production in 2016. Tea prices at the Colombo auctions relatively fluctuate over the time. The change of the tea prices has greater impact on the performances of the entire economy and living standard of the people involved with the industry. The primary objective of this study was to determine the factors that influence the high grown and low grown tea auction price at Colombo auction and to make suggestion or recommendation to reduce the price fluctuation in the Colombo auction. The variables used in this study were auction price of high grown and low grown tea, quantity sold of high grown and low grown tea at Colombo auction, annual production of high grown and low grown tea and cost of production of tea. For this study, secondary time series data for the variables mentioned above were collected from 1998 to 2015 from annual report of Central Bank of Sri Lanka. Cointegration regression model for high grown and low grown tea were developed using fully modified Ordinary Lease Square (OLS) method. This study concluded that there is a long run relationship among the auction price of tea, quantity traded and cost of production. In order to increase the profitability of tea industry, modern technology should be used to lower the cost of production and improve the quality of tea produced. It can be achieved by increasing the yield of tea plantation by practicing modern agronomic practices and employing efficient technology in tea processing.
Keywords: Cointegration model; Colombo auction; Price fluctuation; Tea